Dynamics of Food Consumption in West Java Province - Munida Hasna Shifwatun Najma; Kania Agustini; In In Indah Zakiah; Iwan Setiawan; Ahmad Choibar Tridakusumah (Return : Study of Management, Economic and Bussines, 2025)
West Java Province is the most populous province in Indonesia, facing significant food insecurity challenges, particularly among poor households. With a growing population and increasing poverty rates, understanding food consumption dynamics is critical for policy-making. his study aims to analyze the impact of price, income, and socio-demographic factors on food consumption in poor households in West Java Province, both in urban and rural areas. The analysis method was carried out using the Linear Approximation Almost Ideal Demand System (LA-AIDS) model. The results of the study show that the food consumption of poor households in West Java is generally influenced by the own price of the commodity, the price of other commodities, income, number of household members, type of region (rural/urban), education of the household head (average years of schooling of the head of household) and the type of work of the head of the household (agriculture/nonagriculture). The overall expenditure elasticity of poor households shows the results of positive expenditure elasticity. This means that all groups of food commodities are normal goods and some of them fall into the category of luxury goods. The government should make a policy to control food demand through controlling food prices, through decreasing food prices so that household food demand increases.